Analisis Profil Literasi Numerasi Siswa SD Berdasarkan Kerangka Asesmen Kompetensi Minimum (AKM) - Abdul Majid; Adul Leesen (Lembaga Yasin AlSys, 2026)
Numeracy literacy is a fundamental basic competence for elementary school students in responding to the challenges of everyday life. However, the implementation of numeracy instruction in elementary schools still tends to focus on procedural skills and has not fully developed reasoning abilities in accordance with the demands of the Asesmen Kompetensi Minimum (AKM), as reflected in students’ low ability to solve context- and reasoning-based numeracy problems. This study aimed to analyze the numeracy literacy profile of elementary school students based on the AKM framework. A descriptive method with a qualitative approach supported by quantitative data was employed, conducted at SD 50 Bonto Panno, Pangkep Regency, with 25 Grade V students as participants. Data were collected through an AKM-based numeracy literacy test, observation, and documentation. The data were analyzed by categorizing students’ abilities according to the AKM content, context, and cognitive levels, namely understanding, applying, and reasoning. The results showed that most students demonstrated a moderate level of numeracy literacy; they were relatively capable at the understanding level but experienced difficulties at the applying and reasoning levels, particularly in items with scientific and data contexts. The findings conclude that there is a need to strengthen numeracy instruction oriented toward contextual problem solving and mathematical reasoning. The implications of this study are expected to serve as a reference for teachers and schools in designing numeracy learning strategies aligned with the AKM framework.